Postcolonialism and international development studies: a dialectical exchange? - Strongman, Luke (Third World Quarterly, 2014)
‘Postcolonial studies’ is the term given to the study of diaspora and the ideology of colonialism. Since the 1970s, when postcolonial studies was termed ‘Third World’ literature, and the 1980s, when it became ‘Commonwealth’ literature, the persistence of the framework of centre and margin, coloniser and colonised, has endured as a lens with which to view human identity and cultural expression. However, the relationship of postcolonial studies to international development is less well explored. Much of postcolonial studies is concerned with articulating patterns of gain, loss, inclusion, exclusion, identity formation and change, cultural evolution and human geographical dispersal in the wake of the after-effects of colonial rule. Postcolonial critics examine texts and images in order to make inferences about the significance of cultural identity and expression under these conditions. Often this is with a diachronic view of history. International development studies offers postcolonial critics a synchronic perspective on both the policy and materiality of political ideologies affecting cultural identity and expression. This paper looks at how the relationship between postcolonial and international development studies might be furthered in a dialectical exchange. Postcolonial critics such as Said and Pollard et al offer a critical understanding that informs policy making in international development contexts.